Regulatory fit as a determinant of sport performance: how to succeed in a soccer penalty-shooting - Plessner, Henning; Unkelbach, Christian; Memmert, Daniel; Baltes, Anna; Kolb, Andreas (Psychology of sport and exercise, 2009)
Objectives - According to regulatory focus theory, goal pursuit can be achieved by either keeping a promotion or a prevention focus [Higgins, E. T. (1997). Beyond pleasure and pain. American Psychologist, 52, 1280-1300; Higgins, E. T. (2000). Making a good decision: value from fit. American Psychologist, 55, 1217-1230]. Moreover, it has been assumed that people experience fit when they pursue a goal in a manner that sustains their chronic orientation and that fit has a positive impact on performance. In two studies, we investigated the significance of regulatory focus and fit in the realm of sports performance, such as the success rate in a soccer penalty-shooting task. - Methods and Results - In a pilot study, we assessed the chronic regulatory orientation of 211 athletes from different sports. Among others, we found more promotion focus with attackers than with defenders. In the main study, we assessed the chronic regulatory orientation of 20 soccer players who took part in a penalty-shooting task. For half of them, the task was described in terms of promotion, for the others in terms of prevention. We found a positive impact of regulatory fit on scoring performance. - Conclusions - Our findings demonstrate a great potential of regulatory focus theory for the understanding and enhancement of sport performance. The assessment of athletes' chronic regulatory orientation could be of importance for the selection of athletes, the adjustment of tactics and strategies, and coaches' framing of instructions.